Genetic signatures of socio-communicative abilities in primates. (June 2018) - Staes, Nicky; Bradley, Brenda J; Hopkins, William D; Sherwood, Chet C
Highlights: Humans and other primates share ancestral mechanisms underlying speech and language evolution. Comparing genetic variation in apes can help identify human-specific changes in language genes. Great apes show intriguing inter-specific and intra-specific variation in FOXP2 and AVPR1a genes. Abstract : Although many studies stress the distinctive aspects of human language abilities, others argue that its foundations stem from a complex reconfiguration of ancestral systems that are shared with other species. This homology is crucial for identifying the genetic basis of human language, as much of the current research focuses on the recent evolutionary changes of the human genome. Here we provide a review of studies describing genetic variation related to socio-communicative abilities in great apes. As human language potentially evolved in tandem with changes in social cognition, it is important to expand our candidate gene selection to those associated with both social and communicative skills in nonhuman primates to obtain a more complete picture of the genetic architecture underlying language.